THE FLOUTING OF MAXIMS RELATED TO ITS IMPLICATURE IN COMIC STRIPS - ., Jaufillaili (Perspective Jurnal Pendidikan Bahasa Inggris, 2013)
Humors are often used in a communication process. It is usually used ad medium for conveying messages intended for criticism. Through humor, people are capable to laugh at others who receive the messages as well as themselves in more objective ways. Since humors contain some specific messages, most of them usually break the rule of Maxim created by Grice. This article highlights the maxim broke by humors. Keywords: flouting, maxim, jokes/humor, communication